Peucedanum pradeepianum (Apiaceae: Apioideae), a new species from Western Ghats, India - Prabhukumar, Konickal Mambetta; Hareesh, Vadakkoot Sankaran; Pradeep, Ram; Balachandran, Indira (Phytotaxa, 2020)
A new species, Peucedanum pradeepianum KMP Kumar, Hareesh & Indu sp. nov. from Western Ghats of Kerala, is described and illustrated. The new species is closely related to P. anamallayense and P. dhana var. dhana, but differs in having deeply serrate leaflets, broadly ovate bract, ovate-lanceolate, acute bracteoles, and 3–4 lateral and 4 commissural vittae.